(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2025)
This article analyzes the pedagogical foundations and effective implementation conditions of the cooperative approach in the process of forming and developing practical competence among sports activity specialists. The research highlights the opportunities for enhancing the professional skills of future physical education and sports professionals through methods of group learning, collaborative activities, and peer learning. Furthermore, the study substantiates the significance of the cooperative learning environment in fostering communication culture, collective responsibility, problem-solving abilities, and initiative among students. The article also reveals the role of pedagogical technologies, innovative methods, and reflective analysis in developing practical competence.